Perencanaan Sistem Pengumpulan Minyak Jelantah di RT 05 RW 09 Kelurahan Jaticempaka Bekasi - Fairus, Sirin; Asiah, Nurul; Astuti, Rizki Maryam; Dwi Yulianti, Rindu; Arkana, Arkana; Dwi Saputra, Ridho; Nurfadila, Tasya (LPkM Universitas Bakrie, 2023)
The regional governments of Jaticempaka Subdistrict Bekasi (RT 05 RW 09) were committed to improving their area from pollution due to the disposal of cooking oil waste into the environment. Through collaboration between the government and the Bakrie University PKM team, community service activities in educational efforts regarding the management of cooking oil waste were carried out in RT 05 RW 09 Jaticempaka Subdistrict Bekasi. In the first step, the level of participants’ knowledge regarding cooking oil waste was measured using a questionnaire method. In the second step, the cooking oil damage indicators, health hazards, the impact of disposing of cooking oil waste into the environment, and its recycled products were socialized through interactive discussions. The results given through the questionnaire showed that all participants (n=24) of RT 05 RW 09 Jaticempaka Subdistrict – Bekasi used cooking oil, with an average usage of 1-2 litre in one week. As many as 37% of participants threw the cooking oil waste into the waterways or ground, and 50% threw it into the trash. This phenomenon was because participants did not know how to dispose of cooking oil waste properly, as well as its value-added recycled products. However, all participants agreed to establish the collection system for cooking oil waste disposal in the RT 05 RW 09 area, Jaticempaka Subdistrict - Bekasi. Therefore, through this socialization activity, the 24 participants committed and initiated the collection system of cooking oil waste disposal by collecting it using 2L jerrycans distributed by the committee.